Response of Macro- and Micromechanical Characteristics of Mudstone Under Dynamic Impact Based on FDM-DEM Coupling - Jiangkun Yang; Hongfa Ma; Feng Wang; Yuzhong Shen; Linfeng Shi (Geofluids)
The blasting at a site can cause impact disturbances to an open-pit mine slope. For further study the dynamic mechanical properties of rock masses in open-pit mine slope, in this paper, the mudstone of an open-pit slope in Inner Mongolia Autonomous Region of China was taken as research object. Through an indoor split-Hopkinson impact test and a finite difference method and discrete element method coupling simulation (FDM-DEM), the macro and micro impact mechanical response of mudstone under different impact velocities was studied. The results showed that under dynamic load, mudstone exhibited significant strain rate effects. The postpeak plasticity varied in exponentially increasing changes. The crack propagation process in mudstone can be divided into undamaged, initiation, propagation, and rupture stages. As the impact velocity increased, the initiation stage exhibited more microcracks, and the cracks opening in the rupture stage became larger. The 3D coupling numerical model can satisfy stress effectiveness during the dynamic impact process. During the impact process, microcracks increased sharply before the peak stress, and there was a strain lag between the maximum point of crack increment and the peak point of stress. A large number of internal microcracks developed during the postpeak stage, and the cumulative crack increment exhibited a reverse “Z” shape.